Functional observational battery (FOB) tests using caffeine and chlorpromazine hydrochloride in sprague-dawley rats: Functional observational battery in rats - Baskaran, Subramanian; Prakash Malaiarasan; Sanjaykumar Mansukhlal Paneliya (Cellular and Molecular Biology, 2024)
Caffeine is believed to exert its therapeutic effects by acting as a nonselective, competitive antagonist of adenosine receptors. Chlorpromazine, a phenothiazine, is a classic psychotropic mediator extensively used in the clinical administration of psychotic disorders. This study aimed to validate the procedures used for performing Functional Observational Battery (FOB) tests, to demonstrate the proficiency and interobserver reliability during the FOB tests and also to assess effect on neurobehavioral parameters using positive controls in rats. The rats were administered with Caffeine in Milli-Q water as oral gavage at the dose of 20 mg/kg and Chlorpromazine HCl in 0.9% Saline as intraperitoneal route at the dose of 20 mg/kg. No inter-personnel variability was observed in home cage, handling, open field and sensory reactivity observations recorded in Proficiency test. In conclusion, the known effects of positive controls; caffeine and chlorpromazine HCl on neurobehavioral/Functional Observational Battery parameters including autonomic, neuromuscular and sensory reactivity tests were detected in the current study. FOB test procedures for neurobehavioral, grip strength and motor activity are adequate for the detection of neurotoxic effects of positive controls. No major inter-personnel variability was observed between study personnel in neurobehavioural observations.